2019
DOI: 10.1097/brs.0000000000003021
|View full text |Cite
|
Sign up to set email alerts
|

Identifying Predictors of Higher Acute Care Costs for Patients With Traumatic Spinal Cord Injury and Modeling Acute Care Pathway Redesign: A Record Linkage Study

Abstract: Study Design. Record linkage study using healthcare utilization and costs data. Objective. To identify predictors of higher acute-care treatment costs and length of stay for patients with traumatic spinal cord injury (TSCI). Summary of Background Data. There are few current or population-based estimates of acute hospitalization costs, length of stay, and other outcomes for people with TSCI, on which to base … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
12
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 23 publications
2
12
0
1
Order By: Relevance
“…Regardless of injury incident location, it is evident that there are transport modes and decisions can achieve early and direct SCIU admission with timely surgery. These findings complement previous research showing cost savings and reduced secondary complications achievable by streamlining care pathways 16 for patients with TSCI. Evidence informed policy in health service optimisations can provide timely and definitive surgical treatment for those patients suffering an acute TSCI, leading to improved neurological outcomes and reduced secondary complications and mortality.…”
Section: Resultssupporting
confidence: 88%
See 1 more Smart Citation
“…Regardless of injury incident location, it is evident that there are transport modes and decisions can achieve early and direct SCIU admission with timely surgery. These findings complement previous research showing cost savings and reduced secondary complications achievable by streamlining care pathways 16 for patients with TSCI. Evidence informed policy in health service optimisations can provide timely and definitive surgical treatment for those patients suffering an acute TSCI, leading to improved neurological outcomes and reduced secondary complications and mortality.…”
Section: Resultssupporting
confidence: 88%
“…Triage optimisation using geospatial data and scenario modelling has demonstrated significantly reduced time to SCIU admission in a Canadian study 15 . Similar modelling (without geospatial data) showed that optimizing patient-care pathways can achieve significant health system cost reductions from direct in comparison with indirect admissions to SCIU 16 . Studying individuals with acute traumatic brain injury (TBI), Brown et al 12 found significant disparity in survival rates between rural and urban areas using geospatial analysis.…”
Section: Introductionmentioning
confidence: 92%
“…Regardless of injury incident location, it is evident that there are transport modes and decisions can achieve early and direct SCIU admission with timely surgery. These ndings complement previous research showing cost savings and reduced secondary complications achievable by streamlining care pathways (16) for patients with TSCI. Evidence informed policy in health service optimisations can provide timely and de nitive surgical treatment for those patients suffering an acute TSCI, leading to improved neurological outcomes and reduced secondary complications and mortality.…”
Section: Resultssupporting
confidence: 87%
“…Triage optimisation using geospatial data and scenario modelling has demonstrated signi cantly reduced time to SCIU admission in a Canadian study (15). Similar modelling (without geospatial data) showed that optimizing patientcare pathways can achieve signi cant health system cost reductions from direct in comparison with indirect admissions to SCIU (16). Studying individuals with acute traumatic brain injury (TBI), Brown et al (12) found signi cant disparity in survival rates between rural and urban areas using geospatial analysis.…”
Section: Introductionmentioning
confidence: 95%
“…A generalized linear model with a log-link function and a gamma distribution was performed using Stata Version 16 (StataCorp LLC, Texas, USA) in accordance with best practices for analysis of cost data. [9][10][11] We used a consensus group of experts (PG, JL, MM) to select clinically meaningful variables for inclusion in multivariable regression analyses. We reduced redundancy of the included variables to increase the reliability of the regression analysis, and in doing so we reclassified specific MOIs into broad categories (table 3).…”
Section: Open Accessmentioning
confidence: 99%